His and Hers : How Military Spouses Experience Physical, Psychological, and Relational Health - Buchner, Lisa J. (East Carolina University, 2013)
Within military couples, military personnel and their civilian spouses experience both common and unique complexities due to their connection to the military; however, the literature to date has only scratched the surface in investigating how the health of both members of the couple is influenced by this experience. The purpose of the present study was to extend what is currently known about the interface between biological, psychological, and relational health for military couples. Trends within the literature reveal that civilian spouses often face significant challenges as a result of their connection to the military at a comparable level to their military husbands. The present study found that distress, depression, and physiological stress were significant predictors of wives' relational health factors (i.e., marital quality and marital satisfaction), but did not predict husbands' relational health. It is recommended that systemic assessments be developed to fully capture how each spouse's individual experiences inform the couple's relational health. In addition, general mental health assessments, including distress screenings, should be implemented regularly for civilian spouses seeking services at military medical facilities. Lastly, primary care military medical clinics should adopt an integrated care model to consider and treat medical and mental health concerns concurrently.
Keywords: Individual and family studies; Military studies; Biopsychosocial; Couples; Distress; Heart rate variability; Military; Stress; Soldiers--Family relationships; Soldiers--Health and hygiene; Military spouses--Health and hygiene; Families of military personnel--Health and hygiene; Stress (Physiology); Stress (Psychology)